FRESHWATER ROTIFER: (PART II) A LABORATORY STUDY OF NATIVE FRESHWATER ROTIFERS Brachionus angularis AND B. quadridentatus brevispinus FROM TABASCO - Indy, Jeane Rimber; Paramo Delgadillo, Salomón; Arías Rodríguez, Lenin; Márquez Couturier, Gabriel; Segers, Hendrik; Álvarez González, Carlos Alfonso; Contreras Sánchez, Wilfrido Miguel (Kuxulkab', 2014)
This study is a first report of rotifer form the South of Mexico. The rotifers were collected from the fishponds arround Biological Division, UJAT and we examined their morphometric characters, cultivated and identified them. We conducted experiment at different salt concentrations tested at 0g L–1 water (no add NaCL), 2g L–1, 4g L–1, 6g L–1, 8g L–1, 10g L–1 water. The species were identified as Brachionus angularis Gosse (1851) characterized by having two anterior spines, which are almost invisible while B. quadridentatus brevispinus Ehrenberg (1832) with six anterior spines, which can be seen clearly. Lorica size of B. angularis and B. quadridentatus brevispinus are about 12.14 and 12.8 m, respectively and the size is much smaller than B. plicatilis (Mazatlan strain).